Assessing EFL Learners Ability in the Recognition And Production of Homophones (Journal of the College of Education for Women, 2019)
This study deals with the orthographic processing ability of homophoneswhich can account for variance in word recognition and production skills due tophonological processing. The study aims at: A)Investigating whether the studentscan recognize correct usage and spelling comprehension of different homophonesby using appropriate word that overlapped in both phonology and orthography.B)Assessing spelling production word association to the written form of thehomophone in the sentence comprehension task. To achieve these aims, two testshave been conducted and distributed on 50 students at first stage at the College ofEducation(Ibn-Rushd) for the academic year 2010-2011. The two tests are exposedto a jury of experts for the purpose of ascertaining their validity. The split-halfreliabilities (Spearman-Brown corrected) from this task were .93 and .82,respectively to calculate their reliability coefficient. The results show that there arestatistical differences between the two tests: the recognition test and the productiontest show that the testees have achieved better performance in the recognitiontest(75%)than in the production test (25%) .